2010
DOI: 10.1111/j.1574-6976.2010.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

HowSaccharomyces cerevisiaecopes with toxic metals and metalloids

Abstract: Toxic metals and metalloids are widespread in nature and can locally reach fairly high concentrations. To ensure cellular protection and survival in such environments, all organisms possess systems to evade toxicity and acquire tolerance. This review provides an overview of the molecular mechanisms that contribute to metal toxicity, detoxification and tolerance acquisition in budding yeast Saccharomyces cerevisiae. We mainly focus on the metals/metalloids arsenic, cadmium, antimony, mercury, chromium and selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
215
4
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(240 citation statements)
references
References 304 publications
9
215
4
6
Order By: Relevance
“…To survive the toxicity of these nonessential toxic heavy metals, organisms and cells need to develop efficient detoxification systems. It is suggested that all organisms possess mechanisms to evade heavy metal toxicity and acquire tolerance (Tamás et al, 2005;Wysocki and Tamas, 2010). Although multiple mechanisms appear to be involved in the detoxification of heavy metals (Tamás et al, 2005;Verbruggen et al, 2009), several lines of evidence in this study favor an idea that the cellular MRP/GSH system plays key roles in heavy metal detoxification of zebrafish cells: 1) MRP-like activity exists in zebrafish cells; 2) Enhanced MRP activity is found in cells chronically exposed to cadmium; 3) Inhibition of MRP activity sensitizes ZF4-Cd cells to heavy metals; 4) ZF4-Cd cells exhibit strong ability of heavy metal efflux; 5) Cellular GSH contents are significantly increased in ZF4-Cd cells; 6) Inhibition of GSH biosynthesis and GST activity sensitizes ZF4-Cd cells to heavy metals; and 7) Transcriptional expression of abcc2 and abcc4 genes is constitutively activated in ZF4-Cd cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To survive the toxicity of these nonessential toxic heavy metals, organisms and cells need to develop efficient detoxification systems. It is suggested that all organisms possess mechanisms to evade heavy metal toxicity and acquire tolerance (Tamás et al, 2005;Wysocki and Tamas, 2010). Although multiple mechanisms appear to be involved in the detoxification of heavy metals (Tamás et al, 2005;Verbruggen et al, 2009), several lines of evidence in this study favor an idea that the cellular MRP/GSH system plays key roles in heavy metal detoxification of zebrafish cells: 1) MRP-like activity exists in zebrafish cells; 2) Enhanced MRP activity is found in cells chronically exposed to cadmium; 3) Inhibition of MRP activity sensitizes ZF4-Cd cells to heavy metals; 4) ZF4-Cd cells exhibit strong ability of heavy metal efflux; 5) Cellular GSH contents are significantly increased in ZF4-Cd cells; 6) Inhibition of GSH biosynthesis and GST activity sensitizes ZF4-Cd cells to heavy metals; and 7) Transcriptional expression of abcc2 and abcc4 genes is constitutively activated in ZF4-Cd cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that all organisms possess defensive systems to evade heavy metal toxicity and acquire tolerance (Tamás et al, 2005;Wysocki and Tamas, 2010). The hypothesis is supported by the evidence that cells can develop stable resistance to heavy metals after prolonged and low-level exposure (Brambila et al, 2002;Lee et al, 2006;Vernhet et al, 1999).…”
Section: Introductionmentioning
confidence: 95%
“…Examples of intracellular detoxification mechanisms include efflux, chelation and compartmentalization. In S. cerevisiae, metal removal from the cytosol through export pathways (efflux) was described for As(III) and Cd(II) through the export proteins Acr3p and Pca1p, respectively [11]. The reduction of free metal concentration in the cytosol can occur by metal chelation with low molecular weight, cysteine-rich peptides and proteins, such as glutathione (GSH) and metallothioneins [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several works have shown the role of GSH in the protection of the cells against the damage provoked by oxidative stress [11], xenobiotics, carcinogens, radiation [15] and heavy metals [Cd, As(III), Sb(III), Se and Hg] [6,18,25]. GSH seems to be a key molecule in the defence against oxidative stress and metal toxicity.…”
Section: Introductionmentioning
confidence: 99%